RELASI TRIKOTOMI SEMIOTIKA DALAM CERPEN BABY BLUES KARYA POPPY TRISNAYANTI PUSPITASARI - wini, Haswin Haswin; M.Daut, Suci Pratiwi; Hardianti, Wa Ode (Seshiski: Southeast Journal of Language and Literary Studies, 2023)
The short story "Baby Blues" by Poppy Trisnayanti Puspitasari is a thriller genre with a combination of psychological science. This short story describes the impact of the mental problems of a mother affected by Baby Blues syndrome. The phenomenon of Baby Blues syndrome is very common among young mothers who have just given birth to their first child. There are several phenomena contained in the short story "Baby Blues" by Poppy Trisnayanti Puspitasari which are signs of disturbed mental health. This research uses an inductive qualitative approach, which means developing concepts based on existing data. The explanation in this research uses the aesthetic approach analysis put forward by Charles Sanders Pierce in describing signs which include indexes, icons and symbols in the short story "Baby Blues" by Poppy Trisnayanti Puspitasari which ultimately produces a conclusion. The result of this research is a description of signs which include indexes, icons and symbols in the short story "Baby Blues" by Poppy Trisnayanti Puspitasari. For example, indexes, icons, and symbols the signs obtained predominantly perceive markers of mental health.